Autologous fat grafting for enhancement of breast reconstruction with a transverse myocutaneous gracilis flap: A cohort study. Issue 11 (November 2018) - Russe, Elisabeth; Kholosy, Hassan; Weitgasser, Laurenz; Brandstetter, Michael; Traintinger, Heike; Neureiter, Jennifer; Wechselberger, Gottfried; Schoeller, Thomas
Summary: Background: The transverse myocutaneous gracilis (TMG) flap is a viable option for the reconstruction of small- to moderate-sized breasts. The purpose of this series was to examine the outcomes of fat grafting to breast and donor site secondary to breast reconstruction with a TMG flap. Methods: A cohort study was conducted to identify all patients who underwent autologous fat grafting after breast reconstruction with a TMG flap at two institutions between January 2009 and October 2013. Data were collected regarding patient demographics, body mass index, and medical history as well as surgical details regarding TMG flap surgery and fat grafting. Results: A total of 145 fat graftings were performed in 83 patients following TMG flap breast reconstruction to improve the contour, shape, and volume of breasts (98%, n = 142), donor site (9%, n = 13) or both (7%, n = 10), mainly after breast cancer surgery (83%). On average, 1.8 fat grafting sessions were performed with an average of 30cc fat per breast and 56.4cc fat per thigh. In 72% of patients, fat injection was performed by other pending reconstructive procedures. Fat was harvested by the tumescent technique, by using a filter syringe system, and injected without any further processing in multiple layers. Conclusions: Autologous fat grafting as a secondary procedure represents a powerful adjunct to enhance the aesthetic outcome of the reconstructed breast and donor site. It can be easily combined with other pending reconstructive procedures. With additional fat grafting, it may be possible to expand indications and offer autologous reconstruction with a TMG flap even in very lean patients.